Genetic and phenotypic correlations among lactation traits in Hariana cattle - S. Singh; Z.S. Rana; R. Kumar; B.L. Pander; S.S. Dhaka; B. Prakash (Journal of Livestock Biodiversity, 2025)
The study was conducted on 762 Hariana cows maintained at Government Livestock Farm, Hisar, Haryana (India) with the objectives to study the genetic and phenotypic relationship of first lactation with first four lactation traits like MY, LL, WA, MCI, PY, DP. The estimates of heritability of all lactation traits were of low to moderate magnitude indicating that additive genetic variability for these traits is less. The genetic and phenotypic correlation between lactation traits indicated that PY of first lactation has high genetic and significant phenotypic correlations with MY of cach lactation and negative genetic and phenotypic correlations with DP of each lactation. The results suggested that selection on the basis of MY1 and PY1 would bring genetic improvement in MY of following lactations.